EFEKTIVITAS PEMBELAJARAN KEWIRAUSAHAAN - Jayadi Jayadi; Yuli Triastuti; Sri Lestari Prasilowati (Jurnal Pengembangan Wiraswasta, 2020)
The study was conducted with the aim of finding out whether there were differences in attitudes, motivation, and entrepreneurial interests of STIE IPWIJA students before and after receiving entrepreneurship learning. The research was conducted at the STIE IPWIJA Campus in 2019. The research method used was a comparative study with the Quasi Experiment (One Group Pretest and Postest Design) design. The population in this study were students who were taking Entrepreneurship courses totally of 225 students. The research sample used was 150 students taken by the Cluster Random Sampling technique. Research data were collected through a closed questionnaire given to students before and after taking entrepreneurship courses. The research data were processed by descriptive and inferential analysis using the correlated test formula (t-test) of two samples. Data processing using SPSS software. The results showed that: (1) There were differences in entrepreneurship attitudes of STIE IPWIJA students before and after receiving entrepreneurship course, (2) There were differences in entrepreneurship motivation of STIE IPWIJA students before and after receiving entrepreneurship course, (3) There were no differences in entrepreneurial interest in STIE IPWIJA students before and after receiving entrepreneurship course.Keywords: Effectiveness, Entrepreneurship Learning, Motivation, Attitudes, and Entrepreneurial Interest.  ABSTRAKPenelitian dilaksanakan dengan tujuan untuk mengetahui apakah ada perbedaan sikap, motivasi dan minat berwirausaha mahasiswa STIE IPWIJA sebelum dan sesudah mendapat pembelajaran kewirausahaan. Penelitian dilaksanakan di Kampus STIE IPWIJA Tahun 2019. Metode penelitian yang digunakan adalah studi komparatif dengan desain Quasi Experiment (One Group Pretest and Postest Design). Populasi dalam penelitian adalah mahasiswa  yang sedang  menempuh mata kuliah Kewirausahaan  berjumlah 225. Sampel penelitian yang digunakan sebanyak 150 mahasiswa yang diambil dengan teknik Cluster Random Sampling. Data penelitian dikumpulkan melalui kuesioner tertutup yang diberikan kepada mahasiswa sebelum dan sesudah menempuh mata kuliah kewirausahaan. Data penelitian diolah dengan analisis deskriptif dan inferensial menggunakan rumus uji beda (t-test) dua sampel yang berkorelasi. Pengolahan data menggunakan bantuan software SPSS. Hasil penelitian menunjukkan bahwa: (1) Ada perbedaan sikap berwirausaha mahasiswa STIE IPWIJA sebelum dan sesudah mendapatkan pembelajaran kewirausahaan, (2) Ada perbedaan motivasi berwirausaha mahasiswa STIE IPWIJA sebelum dan sesudah mendapatkan pembelajaran kewirausahaan, (3) Tidak ada perbedaan minat berwirausaha mahasiswa STIE IPWIJA sebelum dan sesudah mendapatkan pembelajaran kewirausahaan.Kata kunci: Efektivitas, Pembelajaran Kewirausahaan, Motivasi, Sikap, dan Minat Berwirausaha.